CINCUENTA AÑOS DE LIBERTAD: LAS IDEAS DE A.S. NEILL Y LA ESCUELA DE SUMMERHILL - Hemmings, Ray ((Alianza Universidad, 1975)
TRADUCCION DE: FIFTY YEARS OF FREEDOM A STUDY OF THE DEVELOPMENT OF THE IDEAS OF A.S. NEILL